ChemInform Abstract: High‐Valent Iron‐Oxo and ‐Nitrido Complexes: Bonding and Reactivity. Issue 47 (3rd November 2016) - Mondal, Bhaskar; Roy, Lisa; Neese, Frank; Ye, Shengfa
Abstract: Review: [47 refs.